2022
DOI: 10.1007/s12311-022-01418-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebello-basal Ganglia Networks and Cortical Network Global Efficiency

Abstract: The cerebellum (CB) and basal ganglia (BG) each have topographically distinct functional subregions that are functionally and anatomically interconnected with cortical regions through discrete thalamic loops and with each other via disynaptic connections, with previous work detailing high levels of functional connectivity between these phylogenetically ancient regions. It was posited that this CB-BG network provides support for cortical systems processing, spanning cognitive, emotional, and motor domains, impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 100 publications
3
14
0
Order By: Relevance
“…We also replicated and extended our prior work detailing correlations between CB-BG and cortical networks (Jackson and Bernard, 2022) by expanding the sample size 3-fold and introducing additional controls to probe the network relationships. We found CCBN GE strongly predicted DMN and AN GE, moderately predicted MN GE, and did not predict EN GE, largely consistent with our previous findings and suggestive of CCBN involvement in self-referential thought and auditory/verbal working memory (Fox et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…We also replicated and extended our prior work detailing correlations between CB-BG and cortical networks (Jackson and Bernard, 2022) by expanding the sample size 3-fold and introducing additional controls to probe the network relationships. We found CCBN GE strongly predicted DMN and AN GE, moderately predicted MN GE, and did not predict EN GE, largely consistent with our previous findings and suggestive of CCBN involvement in self-referential thought and auditory/verbal working memory (Fox et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…The cerebellum (CB) and basal ganglia (BG) are each cytoarchitectonically unique and thought to be foundational to cortical processing, each supporting cognition with specific computations associated with predictive learning (Flanagan and Wing, 1997;Morton and Bastian, 2006;Wolpert et al, 2011) and reinforcement learning (Schultz et al, 1998(Schultz et al, , 2000Cohen and Frank, 2009;Ito and Doya, 2011), respectively. Previous work by our lab found a highly-connected resting-state CB-BG network in healthy young adults (Hausman et al, 2019) and a follow-up study using graph theory metrics confirmed distinct motor and cognitive functional networks that were differentially related to cortical functional networks (Jackson and Bernard, 2022). Notably, the CB and BG have each been separately implicated in multiple psychiatric and neurological disorders (e.g., depression, bipolar disorder, psychosis; reviewed in Ring, 2002;Hoppenbrouwers et al, 2008;Macpherson and Hikida, 2019).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations